New buildings - Unknown:::Creator::::::::::::
Engraving of buildings in Vienna identified by number: 1. St. Charles Church 2. New city theater 3. Polytechnic Institute 4. National bank 5. Theseus, the temple in people's garden 6. Summer palace of Prince Schwarzenburg 7. Schönbrunn.